PTH-001 The learning curve to achieve competency in upper gastrointestinal endoscopy: analysis of completion rates using the jets database. (22nd June 2015) - Ward, ST; Hancox, A; Ismail, T; Valori, R; Dunckley, P
Abstract : Introduction: Endoscopy training programmes assess competency of trainees to perform oesophago-gastric-duodenoscopy (OGD). The Joint Advisory Group (JAG) in the UK require trainees to intubate D2 >95% of the time. Stipulation of a D2 completion rate is necessary but insufficient without specifying the minimum number of procedures over which the target completion rate is to be achieved. The number of OGDs required to achieve competency is not well established. The American Board of Internal Medicine recommends a minimum number of 100 while JAG requires 200. JAG developed a trainee e-portfolio, called the JAG endoscopy training system (JETS) which is used by all endoscopy training units and trainees in the UK. Method: JETS was interrogated to retrieve all OGD records from the time of the inception on 1 st September 2009 to 1 st June 2014. Trainees who had performed a baseline number of >20 procedures or submitted data for less than 20 procedures were excluded. The primary outcome measure was D2 intubation without physical assistance. The number of OGDs to achieve a D2 intubation rate of >95% was calculated by moving average method and learning curve (LC)-Cusum analysis. With regard incomplete OGDs, the extent that trainees reached without assistance was determined. Factors associated with OGD completion were analysed by a mixed effects logistic regression model. Results: 2336 trainees submitted data on 282, 256 OGDs: 1542 trainees had an unknown or baseline number <20. Of these, 1126 had submitted data for >20 procedures. By LC-Cusum, the median number of procedures for competent trainees to attain 95% D2 intubation was 131. After 100 procedures, 66% trainees had attained competency, rising to 89% after 150 procedures. By moving average method, the 95% D2 intubation rate was achieved after 182 procedures. For incomplete OGDs, the extent reached without assistance by trainees was: stomach (45%), oesophagus (24%), D1 (18%), or failed intubation (13%). Factors associated with OGD completion were total number of OGDs performed, previous lower GI endoscopy experience, patient gender, endoscopic diagnosis. Conclusion: This is the largest study on the learning curve to achieve competency at OGD. The number of procedures required for trainees to attain a D2 intubation rate of 95% is between 131 and 182. Although other criteria are required to certify a trainee as competent, this study does provide objective evidence for a benchmark number of procedures. Factors known to be associated with OGD incompletion are the same as those identified here within the learning context. Disclosure of interest: None Declared.